STATE ISLAM AND OPPOSITIONAL ISLAM: The Rearticulation of Islamic Politics From Jokowi to Prabowo in Indonesia - Ahmad Dawam Pratiknyo (SANGKéP: Jurnal Kajian Sosial Keagamaan, 2026)
This article examines the transformation of Islam-state relations in Indonesia through a comparative analysis of two periods of government: Joko Widodo's second term (2019-2024) and the early presidency of Prabowo Subianto (2024-present). Drawing on qualitative library research and critical discourse analysis, this article proposes the conceptual framework of "State Islam" and "Oppositional Islam" to capture dynamics that exceed the conventional secular-religious dichotomy. The findings indicate that political Islam has undergone structural rearticulation rather than depoliticisation. Under Jokowi, the state developed a defensive-combinative strategy that combined legal instruments, the technocratisation of religion through halal certification, and moderate religious discourse to neutralise ideological opposition. Under Prabowo, this strategy has shifted towards proactive co-optation, incorporating key Islamic actors into the governing coalition through institutional access and patronage, thereby blurring the boundary between state and opposition. Theoretically, this study contributes by explaining how religious authority is managed and integrated into state structures. Empirically, it demonstrates that elite co-optation produces internal fragmentation within "State Islam" and leaves a residual, value-based opposition within civil society, with significant implications for democracy and identity politics in Indonesia's compromised democratic landscape.